“There are causes I will lose my job for, you just let me know when you need me”: a creative nonfiction narrative demonstrating how identities and experiences foster solidarity in and create extra work for Queer educators - Dills, Seth M. (Kansas State University, 2023)
Research suggests that there are Queer educators in nearly every school in America (Woog, 1995). With the knowledge that there are Queer educators working within schoolhouses across the nation, it is necessary to understand their experiences in order to close gaps in the literature and to identify implications of the understanding of their experiences. In order to do this, seven Queer educators across the state of Kansas were interviewed, and that interview data was used to identify the findings of this dissertation. Considering how the experiences of Queer educators, who teach in K-12 public schools in Kansas, and how those experiences and identities impact their practice and professional interactions were the goals of this study. By employing a narrative inquiry approach to this research, this dissertation creates an avenue for understanding through storytelling, in that the stories that were told by the participants are gathered and (re)told by the researcher in order to highlight the various narrative threads that give meaning to collective, individual, and varying experiences. The use of Queer Standpoint Theory was used to honor the multiple, fluid, and shifting identities associated with Queer Theory while centering on the Queer identity of the educators as it is locked socioculturally and temporally. Data for this study were collected through the use of responsive interviews (H. J. Rubin & Rubin, 2011) and photo elicitation techniques (Croghan et al., 2008). Data were analyzed and coded for themes in order to explore the various narrative threads that were interwoven between the seven participants. Two themes that are impacted by participants’ experiences and identities were identified, solidarity and more work. The first theme was that Queer educator identities and experiences foster solidarity through a variety of methods, which made up five distinct categories. Queer educators demonstrate solidarity through empathy and awareness, relationships with students, signs and symbols, standing up for the underdog, and acting as a role model. This represents how and why the Queer educators demonstrate solidarity through their actions. The second theme was that Queer educator identities and experiences create extra work for Queer educators in five different ways (categories). The extra work is created by standing up for the underdog, acting as a role model, doing extra mental calculations, acting as a spokesperson, and dealing with homophobia and intolerance. This represents the various tasks that are given to Queer educators, or that Queer educators choose to take on themselves, which require them to do extra work that is not expected of their heterosexual and cisgender counterparts. These findings are described using a creative nonfiction narrative (Gutkind, 2012). The narrative is composed of the words that were used by the participants during interviews that they completed with the researcher. These individual interviewers were compiled, coded, and then arranged in a narrative that describes a fictional scenario where participants joined each other in a special interest group as part of a professional development session. This scenario did not actually occur, but the opportunity to put the participants in conversation with one another allowed for the various narrative threads, contradictions, and segments to be highlighted and demonstrate findings. A variety of models, experiences, approaches, and sociocultural factors are described within this study. This provides an overview of the context in which this study occurred and allows for further contextualization of the participants’ lived experiences as they are (re)told and (re)presented. In addition to the findings of this study, limitations, implications, and areas of future research are also described.
Keywords: Queer; LGBTQ+; Educators; Teachers; Queer standpoint theory; Creative nonfiction